2015
DOI: 10.11301/jsfe.16.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermolecular Interactions on Water Activity of Multicomponent Aqueous Solutions

Abstract: Water activity (a w ) was measured for various two component aqueous solutions at various intersolute interactions and the obser ved a w was compared with the theoretical prediction by Ross equation assuming no inter-solute interactions. For solutions with neutral components including electrolytes, sugars, and neutral amino acid, solute-solute interaction was weak so that no substantial deviation was observed for observed a w from that predicted by Ross equation. When acid and base were involved, the deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…From the above, it can be concluded that the G index is able to capture the molecular features of the solutes that mostly affect the water network structure, and, thus, water activity [7,9,39]. Finally, a comparison of the performance of models containing G with those including I AC and Z 1 suggests that there is no loss of information when the two indices are combined into a single one.…”
Section: Correlation Of Water Activity Datamentioning
confidence: 90%
“…From the above, it can be concluded that the G index is able to capture the molecular features of the solutes that mostly affect the water network structure, and, thus, water activity [7,9,39]. Finally, a comparison of the performance of models containing G with those including I AC and Z 1 suggests that there is no loss of information when the two indices are combined into a single one.…”
Section: Correlation Of Water Activity Datamentioning
confidence: 90%
“…Although a theoretical incompleteness has been pointed out for Eq. 5 (Lilley, 1987), this equation was proved to be useful in practice unless a very strong solute-solute interaction exists (Chen, 1990;Sone et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such an interpretation suggests that water activity should therefore predominantly be a function of water-water interaction, with increased interaction (i.e., more order or structure) leading to a reduction in water activity ( Caurie, 2005 , Dutkiewicz and Jakubowska, 2002 ). Even though the contribution from solute-solute interaction is acknowledged to be present in water activity this contribution is considered to be small and negligible ( Sato and Miyawaki, 2008 , Sone et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%